Analisis Mapping Cakupan Sinyal SSID Dengan Metode PPDIOO Untuk Mendukung Pelaksanaan Ujian Semester Sekolah Menggunakan Smartphone Android - Ahmad Tantoni; Mohammad Taufan Asri Zaen; Khairul Imtihan (STMIK Budi Darma, 2022)
In this modern era of the industrial revolution 4.0, high school level exams which used to still use paper to print question sheets were then given to students and students answered the question sheet on the answer sheet provided by the exam supervisor/committee. It was began to be replaced by the existence of information systems (IS) and information technology (IT) which made it easier in terms of time and cost efficiency. With the application of IS/IT, it supports major changes in carrying out the exams conducted by high school level schools, also supported by millennial children aged 14 to 19 years who already have smartphones in their hands. SMAN 1 Masbagik is a public high school located in Masbagik sub-district, East Lombok with a land area of 10,260 m2 where there are 30 classrooms and 5 laboratory rooms. From the results of interviews with teachers at SMAN 1 Masbagik, it was found that almost 80% of students have smartphones, this is very supportive of the transition from manual exams to computer/smartphone-based exams. From the survey of the location of SMAN 1 Masbagik, it was found that there were access points installed in all classes to support computer-based exams intended for all students to access the local question server that had been provided. However, there are also problems found when conducting a direct survey to the location to interview students in the problem of wireless signal strength (access points) which are spread across each class unevenly/all over to students' smartphones, there are blank spots in some classes which result in students experiencing delays. data transmission when filling out the answers to questions on their respective smartphones. In wireless signal technology, interference also occurs, according to S'to, explaining that the frequency allocator for each channel used overlaps, for example, the use of channel 1 and channel 2 simultaneously can cause interference which results in data being sent will be damaged. This can also reduce data transfer from the access point to the smartphone to be slow. The method used is the PPDIOO method (Prepare, Plan, Design, Implement, Operate and Optimize), but there is a limitation of the method only to the design stage. The purpose of this research is to be considered for schools to determine the position of a good access point and cover all areas of the classroom so that the exams conducted by the education unit are successful and analyze the selection of channel widths to avoid wireless signal interference. The test results while getting a bad signal in the corner of the class and even blank spots in some places.